Effectiveness of fingerprint and mobile attendance systems in improving academic service quality in higher education - Radhi, Fahrul; Aminah, Siti; Safiah, Intan; Ikhwan, M. (Geuthèë Institute, Aceh, 2025)
This study analyzes the effectiveness of fingerprint-based biometric attendance and the SIMKULIAH Mobile Attendance system in improving academic service quality at the Faculty of Teacher Training and Education (FKIP), Universitas Syiah Kuala. Respondents consisted of 170 lecturers selected from a population of 1,773 using purposive sampling. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that both attendance systems significantly enhance academic service quality; the fingerprint system contributes primarily to accuracy, accountability, and data security (β = 0.308), whereas the mobile attendance system demonstrates a stronger influence (β = 0.435) due to its higher accessibility, flexibility, and real-time integration with academic information services. These results indicate that mobile-based attendance provides a more adaptive and efficient solution for daily academic administration, while fingerprint verification remains valuable for ensuring data integrity. The study offers practical implications for digital attendance management and highlights the need for institutional policies, reliable infrastructure, and user readiness to support effective system implementation in higher education.